STRATEGI BERTAHAN HIDUP NELAYAN TRADISIONAL DI PELABUHAN LEPPE’E KABUPATEN BULUKUMBA - Astita; Sitti Aisyah BM; Sakaruddin Mandjarreki (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
The journal that was made aims to describe the survival strategy of traditional fishermen in the port of Leppe'e, Bulukumba Regency. Leppe'e Harbor is a settlement or neighborhood for traditional fishermen workers in the Regency. In addition, Leppe'e Port is a means of transportation between goods and services for large-scale shipments outside the region. In addition to the environment, the port of Leppe'e is a place for traditional fishermen, both laborers and individual fishermen, who have very minimal poverty levels both in terms of income and so on. This study aims to determine the factors that cause poverty of traditional fishermen and the survival strategies of traditional fishermen in Leppe'e Port, Bulukumba Regency. This study uses a sociological approach with descriptive qualitative research types and data collection techniques used in this study are interview observation and documentation. This research was conducted at the Port of Leppe'e Regency